Maskulinitas dan Hubungan Interpersonal Perspektif Al-Qur’an - Lestari, Rosa (Universitas Islam Negeri Madura, 2025)
During this discussion, gender is only been about women because in the past (before the 19th century) women were not respected. So that the existence of men and their roles in the present (21st century AD) have received less attention to be studied as a special education, even though it is clear in the Qur'an, Surah An-Nisa verse 34, that